PENERAPAN STRATEGI REACT (RELATING, EXPERIENCING, APPLYING, COOPERATING, AND TRANSFERRING) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID DI KELAS XI MIA SMA NEGERI 2 PEKANBARU - Nurmawiyanti, Tuti; Azmi, Johni; Amran, Elva Yasmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : It has been applied the REACT strategy to improve students learning achievement on the subject of colloid in class XI MIA SMAN 2 Pekanbaru. The research is an experimental research with pretest-posttest design. The samples of this research were the students of class XI MIA4 as the experimental class and the students of class XI MIA1 as the control class. They were randomly determined after given the tests of normality and homogeneity. Experimental class is a class which was given a treatment by applying REACT strategy in learning process. The data were analyzed by using t-test. Based on the result of data analysis, it obtained tscore > ttable (2,73 > 1,67), it means that the application of REACT strategy can improve student learning achievement on the subject of colloid in class XI MIA SMAN 2 Pekanbaru. The improvement category of student achievement at experiment class was high category with normalized N-gain which is 0,73.Key Words : REACT strategy, Learning Achievement, Colloid